Cross Cultural Adaptation of Academic Emotion Regulation Questionnaire (AERQ) in the Indian Context - Chechi, Vijay Kumar; Chakraborty, Rajib; Chakraborty, Rajib (International Journal of Psychosocial Rehabilitation, 2020)
The researchers tried to adapt and validate the Academic emotion regulation questionnaire (AERQ) developed by Buric, Soric and Penezic (2016), in the present study in the Indian context. The sample of the study comprised of 496 students (330 boys and 5 girls from Mechanical engineering and 127 boys and 34 girls from Hotel management) of Lovely Professional University, India. The EFA performed using “SPSS Statistics Ver. 23.0” revealed the original factors as mentioned in the original tool with 53.402 % total variance explained. The factor structure was later tested using Confirmatory factor analysis with the help of “SPSS AMOS Ver. 23.0”. The “goodness of fit” estimates were moderate but with strong factor loadings, akin to the original study. Internal consistency of the eight dimensions ranged from 0.594 to 0.833. Implications of the study are discussed.